Low Risk of Primary Clostridium difficile Infection With Tetracyclines: A Systematic Review and Metaanalysis. (18th September 2017) - Tariq, Raseen; Cho, Janice; Kapoor, Saloni; Orenstein, Robert; Singh, Siddharth; Pardi, Darrell S; Khanna, Sahil
Abstract : Literature describing the choice of antibiotic to minimize Clostridium difficile infection (CDI) is scarce. Tetracyclines may be associated with a lower risk of CDI compared with other antibiotics. It may be reasonable to use tetracyclines preferentially to reduce CDI risk. Abstract: Background: The choice of antibiotics for systemic infections in patients with a high risk of Clostridium difficile infection (CDI) remains a clinical practice dilemma. Although some studies suggest that tetracyclines may be associated with a lower risk of CDI than other antibiotics, other results are conflicting. We conducted a systematic review and metaanalysis of studies that assessed the risk of CDI with tetracyclines compared to other antibiotics. Methods: We conducted a systematic search of Medline, Embase, and Web of Science from January 1978 through December 2016 to include studies that assessed the association between tetracycline use and risk of CDI. Weighted summary estimates were calculated using generalized inverse variance with a random-effects model using RevMan 5.3. Study quality was assessed using the Newcastle-Ottawa scale. Results: Six studies (4 case control, 2 cohort) with patient recruitment between 1993 and 2012 were included. Metaanalysis using a random-effects model, demonstrated that tetracyclines were associated with a decreased risk of CDI (odds ratio [OR], 0.62; 95% confidence interval [CI], 0.47–0.81; P < .001). There was significant heterogeneity, with an I 2 of 53% with no publication bias. Subgroup analysis of studies that evaluated the risk of CDI with doxycycline alone also demonstrated a decreased risk of CDI (OR, 0.55; 95% CI, 0.40–0.75; P < .001). Conclusions: Metaanalyses of existing studies suggest that tetracyclines may be associated with a decreased risk of CDI compared with other antimicrobials. It may be reasonable to use tetracyclines whenever appropriate to decrease CDI associated with antibiotic use.